Introduction to graphene-based nanomaterials : from electronic structure to quantum transport - Fo T̉orres, Luis E. F author; Roche, Stephan author; Charlier, Jean-Christophe author (Cambridge, United Kingdom : Cambridge University Press, 2014)
Includes bibliographical references and index .